2022
DOI: 10.1186/s12906-022-03785-w
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin ameliorates acute lung injury in a rat model of hepatopulmonary syndrome

Abstract: Background Common bile duct ligation (BDL) is a rat experimental model to induce biliary cirrhosis. Lung fibrosis and pulmonary vascular angiogenesis and congestion are the most common complications of biliary cirrhosis that is known as hepatopulmonary syndrome. The aim of the present work is to investigate the acute lung injury in a BDL model and to investigate the possible protective effect of quercetin on this injury. Methods Twenty-four adult m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…These effects are mediated through the NF-κB [ 25 ] and MAPKs pathways, resulting in anti-inflammatory effects on Klebsiella-infected mice [ 26 ]. Quercetin [ 27 , 28 ], rutin [ 29 , 30 ], and kaempferide [ 31 ], all flavonoids, have anti-inflammatory properties to ameliorates acute lung injury. Khazdair Mohammad et al demonstrated that quercetin can reduce the levels of reactive oxygen species, as well as the expression of inducible nitric oxide synthase and pro-inflammatory mediators such as TNF-α, IL-1α, IL-1β, IL-6, IL-10, and IL-12.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are mediated through the NF-κB [ 25 ] and MAPKs pathways, resulting in anti-inflammatory effects on Klebsiella-infected mice [ 26 ]. Quercetin [ 27 , 28 ], rutin [ 29 , 30 ], and kaempferide [ 31 ], all flavonoids, have anti-inflammatory properties to ameliorates acute lung injury. Khazdair Mohammad et al demonstrated that quercetin can reduce the levels of reactive oxygen species, as well as the expression of inducible nitric oxide synthase and pro-inflammatory mediators such as TNF-α, IL-1α, IL-1β, IL-6, IL-10, and IL-12.…”
Section: Discussionmentioning
confidence: 99%